PENGARUH AI FEEDBACK DAN MOTIVASI BELAJAR TERHADAP KETERAMPILAN MENULIS AKADEMIK MAHASISWA JURUSAN PENDIDIKAN AKUNTANSI ANGKATAN 2022 DENGAN MEDIASI SELF-CONFIDENCE - Rahayu; Latifah, Lyna (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
In today’s rapidly evolving educational landscape, academic writing skills are a requirement that students must meet. This study aims to analyze the influence of AI feedback and learning motivation on students’ academic writing skills, with self-confidence serving as a mediating variable. The research problem stems from low writing skills, where only 2 out of 30 students have ever published in a SINTA journal, amidst advancements in AI that offer real-time feedback to address conventional delays. The study employs a quantitative approach with a correlational design. The study population consists of 168 students from the Accounting Education Department, Class of 2022, at Semarang State University, with a sample of 118 respondents selected using purposive sampling. Data were collected via a Likert-scale questionnaire and analyzed using the Partial Least Squares-Structural Equation Modeling (PLS-SEM) method. The results indicate significant direct effects: AI feedback (t=2.618, p=0.010), learning motivation (t=4.052, p=0.000), and self-confidence (t=2.682, p=0.008) on writing skills; AI feedback (t=3.899, p=0.000) and motivation (t=5.792, p=0.000) on self-confidence. Indirectly, self-confidence mediates the effects of AI feedback (t=2.168, p=0.032) and motivation (t=2.541, p=0.012) on writing skills. These findings indicate that the use of AI technology, supported by learning motivation and self-confidence, can optimally enhance students’ academic writing skills.